Abnormal Expression of TRAIL Receptors in Decidual Tissue of Chlamydia trachomatis-Infected Rats During Early Pregnancy Loss. (July 2017) - Lu, Jinzhi; Zhu, Liya; Zhang, Lei; Jiang, Jinpeng; Xie, Fang; Huang, Qing; Li, Xiaolan; Yi, Cunjian
Chlamydia trachomatis is the scientific name of pathogenic bacteria causing infection that has been linked to spontaneous abortion. In this study, the expression pattern of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL; a cytokine related to cell apoptosis) and its receptors was monitored in the decidua of C trachomatis -infected pregnant rats during early gestation to investigate the potential role of this molecular system in C trachomatis -induced spontaneous abortion. The data showed that C trachomatis infection significantly altered the messenger RNA (mRNA) expression of the receptors; death receptor (DR) 4 and DR5 increased, but decoy receptor (DcR) 1 and DcR2 decreased. Consistent with mRNA data, immunohistochemical staining of TRAIL and its receptors indicated that both DR4 and DR5 protein levels were elevated in infected tissues, primarily, decidual cells, decidual vessel wall, and uterine glands, whereas DcR1 and DcR2 showed lower levels compared to the noninfected group. Although receptor expression was altered, there was no difference detected in TRAIL expression. The observed altered expression of TRAIL receptors in C trachomatis -infected rats compared to noninfected rats during the embryo implantation phase suggests a possible mechanism for spontaneous abortion due to apoptosis and therefore failed embryo implantation. In addition, the observed increase in caspase-3 levels in infected cells further supports this finding. Taken together, the data presented in this study suggests C trachomatis infection altered the expression of TRAIL receptors, thus representing a general mechanism for C trachomatis -induced spontaneous abortion in C trachomatis -infected rats during early pregnancy loss.